2020
DOI: 10.22146/ijcn.49696
|View full text |Cite
|
Sign up to set email alerts
|

Faktor sosial, ekonomi, dan pemanfaatan posyandu dengan kejadian stunting balita keluarga miskin penerima PKH di Palembang

Abstract: Social, economic factors, and utilization of posyandu towards stunting among toddlers of poor families of PKH recipients in PalembangBackground: Stunting is a nutritional problem caused by chronic malnutrition. Stunting can result in decreased concentration, memory damage, decreased learning, and school performance, decreased cognitive function, impaired motor development, and has a long-term impact on reducing productivity, thus inhibiting economic growth and causing intergenerational poverty. Stunting can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1
25

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
3
7
1
25
Order By: Relevance
“…The effect is on the distribution of food for children. Rahmawati et al and Wicaksono and Harsanti reported results that are different from this study on the correlation between number of family members and stunting incidence [15], [16].…”
Section: Number Of Family Memberscontrasting
confidence: 96%
“…The effect is on the distribution of food for children. Rahmawati et al and Wicaksono and Harsanti reported results that are different from this study on the correlation between number of family members and stunting incidence [15], [16].…”
Section: Number Of Family Memberscontrasting
confidence: 96%
“…A study in Belu District, East Nusa Tenggara also obtains an insignificant relationship between visits to Posyandu and stunting [31]. However, a study children in Palembang manages to record increased risk of stunting by 3.5 times in children without regular visits to the Posyandu and by 5.2 times in children who never visited the Posyandu [32].…”
Section: Relationship Between Visit Posyandu With Stunting Incidencementioning
confidence: 94%
“…Pengetahuan faktor risiko dan dampak stunting salah satunya dapat dilihat dari faktor pendidikan ibu karena memiliki hubungan paling dominan dengan kejadian stunting yang dialami oleh anak. Ibu dengan pendidikan yang baik cenderung lebih sadar akan kesehatan anak-anaknya (Rahmawati, Fajar, & Idris, 2020;Setiawan, Machmud, & Masrul, 2018).…”
Section: Perilaku Dalam Upaya Pencegahan Stuntingunclassified